Rezolvati ecuatia : (x-3) supra 3 -(1-x)(x+1) supra 2 =(5x-1)(x+2) supra 6 -3
Răspunsuri la întrebare
Răspuns de
8
(x-3)/3 -(1-x)(x+1)/2 =(5x-1)(x+2)/6 -3
2x-6-3+3x²=5x²-x+10x-2-18
2x-9+3x²=5x²+9x-20
2x²+7x-11=0
Δ=7²+4×11×2=49+88=137
x₁=(-7+√137)/2
x₂=(-7-√137)/2
2x-6-3+3x²=5x²-x+10x-2-18
2x-9+3x²=5x²+9x-20
2x²+7x-11=0
Δ=7²+4×11×2=49+88=137
x₁=(-7+√137)/2
x₂=(-7-√137)/2
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă